Time and Age Trends in Free Sugar Intake from Food Groups among Children and Adolescents between 1985 and 2016 - Perrar, Ines; Schadow, Alena M.; Schmitting, Sarah; Buyken, Anette; Alexy, Ute (Nutrients)
Trend analyses suggest that free sugar (FS) intake—while still exceeding 10%E—has decreased among German children and adolescents since 2005, yet that intakes may shift from sugars naturally occurring in foods to added sugars as children age. Thus, we analysed time and age trends in FS intake (%E) from food groups among 3–18 year-olds (1985–2016) using 10,761 3-day dietary records from 1312 DONALD participants (660 boys, 652 girls) by use of polynomial mixed-effects regression models. Among girls, FS from sugar & sweets decreased from 1985 to 2016 (linear trend p < 0.0001), but not among boys (p > 0.05). In the total sample, FS intake from juices increased until 2000 and decreased since 2005 (linear, quadratic trend p < 0.0001). FS from sugar sweetened beverages (SSB) decreased non-linearly from 1985 to 2016 (girls: linear, quadratic, cubic trend p < 0.0001; boys: linear, quadratic, cubic trend p < 0.02). Younger children consumed more FS from juices than older ones, who had a higher FS intake from SSB. FS intake from sugar & sweets increased until early adolescence and decreased afterwards. Since sugar & sweets represent the main source of FS intake and the source with the least pronounced decline in intake, public health measures should focus on these products.

Assessing causal links between metabolic traits, inflammation and schizophrenia: a univariable and multivariable, bidirectional Mendelian-randomization study - Lin, Bochao D; Alkema, Anne; Peters, Triinu; Zinkstok, Janneke; Libuda, Lars; Hebebrand, Johannes; Antel, Jochen; Hinney, Anke; Cahn, Wiepke; Adan, Roger; Luykx, Jurjen J (International Journal of Epidemiology)
Abstract Background Blood immunoreactive biomarkers, such as C-reactive protein (CRP), and metabolic abnormalities have been associated with schizophrenia. Studies comprehensively and bidirectionally probing possible causal links between such blood constituents and liability to schizophrenia are lacking. Methods To disentangle putative causal links between CRP blood levels and schizophrenia in both directions, we conducted multiple univariable Mendelian-randomization (MR) analyses, ranging from fixed-effect to inverse variance-weighted (IVW), weighted-median, MR Egger and generalized summary-data-based Mendelian-randomization (GSMR) models. To prioritize metabolic risk factors for schizophrenia, a novel multivariable approach was applied: multivariable Mendelian-randomization–Bayesian model averaging (MR-BMA). Results All forward univariable MR analyses consistently showed that CRP has a protective effect on schizophrenia, whereas reverse MR analyses consistently suggested absent causal effects of schizophrenia liability on CRP blood levels. Using MR-BMA, as the top protective factors for schizophrenia we prioritized leucine and as the prime risk-factor triglycerides in medium very-low-density lipoprotein (VLDL). The five best-performing MR-BMA models provided one additional risk factor: triglycerides in large VLDL; and two additional protective factors: citrate and lactate. Conclusions Our results add to a growing body of literature hinting at metabolic changes—in particular of triglycerides—independently of medication status in schizophrenia. We also highlight the absent effects of genetic liability to schizophrenia on CRP levels.

Effects of LC-PUFA supply via complementary food on infant development—a food based intervention (RCT) embedded in a total diet concept - Kalhoff, Hermann; Mesch, Christina M.; Stimming, Madlen; Israel, Andreas; Spitzer, Christoph; Beganovic, Latifa; Perez, Rocio Estella; Koletzko, Berthold; Warschburger, Petra; Kersting, Mathilde; Libuda, Lars (European Journal of Clinical Nutrition)

Verbraucherbildung als Bildung für Lebensführung - Schlegel-Matthies, Kirsten (Verbraucherbildung: Ein weiter Weg zum mündigen Verbraucher)

Haushaltsbezogene Bildung – quo vadis? Daseinsvorsorge und Lebensführung im Wandel - Schlegel-Matthies, Kirsten (Haushalt in Bildung & Forschung)
Der Beitrag geht der Frage nach, wie haushaltsbezogene Bildung als Ernährungs- und Verbraucherbildung umgesetzt werden kann, damit Jugendliche selbstbestimmt und verantwortlich ihre individuellen Vorstellungen von einem „guten“ und „gelingenden“ Leben umsetzen können. Die Auseinandersetzung mit dem Zusammenwirken von gesellschaftlicher Lebensweise, privater Lebensführung und individuellen Lebensstilen erweist sich dabei als bedeutsam.

Dietary Glycemic Index and Load and the Risk of Type 2 Diabetes: A Systematic Review and Updated Meta-Analyses of Prospective Cohort Studies - Livesey, Geoffrey; Taylor, Richard; Livesey, Helen F.; Buyken, Anette; Jenkins, David J. A.; Augustin, Livia S. A.; Sievenpiper, John L.; Barclay, Alan W.; Liu, Simin; Wolever, Thomas M. S.; Willett, Walter C.; Brighenti, Furio; et al. (Nutrients)
Published meta-analyses indicate significant but inconsistent incident type-2 diabetes (T2D)-dietary glycemic index (GI) and glycemic load (GL) risk ratios or risk relations (RR). It is now over a decade ago that a published meta-analysis used a predefined standard to identify valid studies. Considering valid studies only, and using random effects dose–response meta-analysis (DRM) while withdrawing spurious results (p < 0.05), we ascertained whether these relations would support nutrition guidance, specifically for an RR > 1.20 with a lower 95% confidence limit >1.10 across typical intakes (approximately 10th to 90th percentiles of population intakes). The combined T2D–GI RR was 1.27 (1.15–1.40) (p < 0.001, n = 10 studies) per 10 units GI, while that for the T2D–GL RR was 1.26 (1.15–1.37) (p < 0.001, n = 15) per 80 g/d GL in a 2000 kcal (8400 kJ) diet. The corresponding global DRM using restricted cubic splines were 1.87 (1.56–2.25) (p < 0.001, n = 10) and 1.89 (1.66–2.16) (p < 0.001, n = 15) from 47.6 to 76.1 units GI and 73 to 257 g/d GL in a 2000 kcal diet, respectively. In conclusion, among adults initially in good health, diets higher in GI or GL were robustly associated with incident T2D. Together with mechanistic and other data, this supports that consideration should be given to these dietary risk factors in nutrition advice. Concerning the public health relevance at the global level, our evidence indicates that GI and GL are substantial food markers predicting the development of T2D worldwide, for persons of European ancestry and of East Asian ancestry.

Dietary Glycemic Index and Load and the Risk of Type 2 Diabetes: Assessment of Causal Relations - Livesey, Geoffrey; Taylor, Richard; Livesey, Helen F.; Buyken, Anette; Jenkins, David J. A.; Augustin, Livia S. A.; Sievenpiper, John L.; Barclay, Alan W.; Liu, Simin; Wolever, Thomas M. S.; Willett, Walter C.; Brighenti, Furio; et al. (Nutrients)
While dietary factors are important modifiable risk factors for type 2 diabetes (T2D), the causal role of carbohydrate quality in nutrition remains controversial. Dietary glycemic index (GI) and glycemic load (GL) have been examined in relation to the risk of T2D in multiple prospective cohort studies. Previous meta-analyses indicate significant relations but consideration of causality has been minimal. Here, the results of our recent meta-analyses of prospective cohort studies of 4 to 26-y follow-up are interpreted in the context of the nine Bradford-Hill criteria for causality, that is: (1) Strength of Association, (2) Consistency, (3) Specificity, (4) Temporality, (5) Biological Gradient, (6) Plausibility, (7) Experimental evidence, (8) Analogy, and (9) Coherence. These criteria necessitated referral to a body of literature wider than prospective cohort studies alone, especially in criteria 6 to 9. In this analysis, all nine of the Hill’s criteria were met for GI and GL indicating that we can be confident of a role for GI and GL as causal factors contributing to incident T2D. In addition, neither dietary fiber nor cereal fiber nor wholegrain were found to be reliable or effective surrogate measures of GI or GL. Finally, our cost–benefit analysis suggests food and nutrition advice favors lower GI or GL and would produce significant potential cost savings in national healthcare budgets. The high confidence in causal associations for incident T2D is sufficient to consider inclusion of GI and GL in food and nutrient-based recommendations.

Developmental trajectories of body mass index from childhood into late adolescence and subsequent late adolescence–young adulthood cardiometabolic risk markers - Oluwagbemigun, Kolade; Buyken, Anette; Alexy, Ute; Schmid, Matthias; Herder, Christian; Nöthlings, Ute (Cardiovascular Diabetology)

Vitamin D and the Risk of Depression: A Causal Relationship? Findings from a Mendelian Randomization Study - Libuda, Lars; Laabs, Björn-Hergen; Ludwig, Christine; Bühlmeier, Judith; Antel, Jochen; Hinney, Anke; Naaresh, Roaa; Föcker, Manuel; Hebebrand, Johannes; König, Inke R.; Peters, Triinu (Nutrients)
While observational studies show an association between 25(OH)vitamin D concentrations and depressive symptoms, intervention studies, which examine the preventive effects of vitamin D supplementation on the development of depression, are lacking. To estimate the role of lowered 25(OH)vitamin D concentrations in the etiology of depressive disorders, we conducted a two-sample Mendelian randomization (MR) study on depression, i.e., “depressive symptoms” (DS, n = 161,460) and “broad depression” (BD, n = 113,769 cases and 208,811 controls). Six single nucleotide polymorphisms (SNPs), which were genome-wide significantly associated with 25(OH)vitamin D concentrations in 79,366 subjects from the SUNLIGHT genome-wide association study (GWAS), were used as an instrumental variable. None of the six SNPs was associated with DS or BD (all p > 0.05). MR analysis revealed no causal effects of 25(OH)vitamin D concentration, either on DS (inverse variance weighted (IVW); b = 0.025, SE = 0.038, p = 0.52) or on BD (IVW; b = 0.020, SE = 0.012, p = 0.10). Sensitivity analyses confirmed that 25(OH)vitamin D concentrations were not significantly associated with DS or BD. The findings from this MR study indicate no causal relationship between vitamin D concentrations and depressive symptoms, or broad depression. Conflicting findings from observational studies might have resulted from residual confounding or reverse causation.

Risk factors for a low weight gain in the early stage of adolescent anorexia nervosa inpatient treatment: findings from a pilot study - Knoll-Pientka, Nadja; Bühlmeier, Judith; Peters, Triinu; Albrecht, Muriel; Adams, Frederike; Wustrau, Katharina; Teufel, Martin; Hebebrand, Johannes; Föcker, Manuel; Libuda, Lars (Eating and Weight Disorders - Studies on Anorexia, Bulimia and Obesity)